2000
DOI: 10.1128/jcm.38.4.1681-1683.2000
|View full text |Cite
|
Sign up to set email alerts
|

G and P Genotyping of Rotavirus Strains Circulating in France over a Three-Year Period: Detection of G9 and P[6] Strains at Low Frequencies

Abstract: Rotavirus G and P types from 716 children with acute diarrhea in Dijon from 1995 to 1998 and throughout France during the winter of 1997-1998 were analyzed by reverse transcription-PCR. P[8],G1 predominated, followed by P[8],G4, which emerged during the last winter. G9 and P[6] strains were detected at low frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…At present, there are 15 G types [29], with G1, G2, G3 and G4 being the predominant ones throughout the world [6]. However, there have been reports of infections by unusual G types [30–35], and recently there have been reports of the emergence of serotype G9 in several countries, such as Brazil [32], Malawi [35], the USA [36,37], France [38], India [39], Argentina [40], the UK [41] and Australia [42].…”
Section: Description Of the Agentsmentioning
confidence: 99%
“…At present, there are 15 G types [29], with G1, G2, G3 and G4 being the predominant ones throughout the world [6]. However, there have been reports of infections by unusual G types [30–35], and recently there have been reports of the emergence of serotype G9 in several countries, such as Brazil [32], Malawi [35], the USA [36,37], France [38], India [39], Argentina [40], the UK [41] and Australia [42].…”
Section: Description Of the Agentsmentioning
confidence: 99%
“…Epidemiological studies have demonstrated that rotavirus G serotypes G1, G2, G3, G4, and P serotypes P1A [8], P1B[4] are the most frequent types associated with disease globally, and are thus the targets for vaccine development [Hoshino and Kapikian, 2000;Kapikian et al, 2001;Hoshino et al, 2002]. Occasionally, unusual rotavirus serotypes, such as G5 and G8, may be locally widespread [Gouvea et al, 1994;Leite et al, 1996;Adah et al, 1997;Nakata et al, 1999;Steele et al, 1999Steele et al, , 2002Hoshino and Kapikian, 2000;Palombo et al, 2000a], whereas evidence has been collected showing a global spread of the G9 serotype, that is considered the fifth most common rotavirus G type worldwide [Leite et al, 1996;Ramachandran et al, 1996Ramachandran et al, , 1998Arista et al, 1997;Unicomb et al, 1999;Bon et al, 2000;Cubitt et al, 2000;Maneekarn and Ushijima, 2000;O'Halloran et al, 2000;Oka et al, 2000;Palombo et al, 2000b;Widdowson et al, 2000;Bok et al, 2001;Cascio et al, 2001;Santos et al, 2001;Cunliffe et al, 2001a,b;Kang et al, 2002;Steele et al, 2002] (V. Martella, personal observations). The mechanisms driving evolution of rotaviruses are various and accumulation of single-point substitutions and reassortment are most likely involved in generating variability [Estes, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Although 10 G-types and 10 P-types have been reported from human [Pongsuwanna et al, 2002], G1-G4 serotypes and P[8] and P [4] genotypes are the most important strains clinically and epidemiologically reported from all countries Palombo, 1999]. However, the pattern of G-type distribution seems to be changing as some unusual types (G5, G8, and G9) and rare combination of G-and P-types have been reported from different countries [Unicomb et al, 1999;Bon et al, 2000;Cubitt et al, 2000;O'Halloran et al, 2000;Palombo et al, 2000;Ramachandran et al, 2000;Bok et al, 2001;Cunliffe et al, 2001;Santos et al, 2001]. New rotavirus strains may evolve through reassortment between gene segments, as well as by accumulation of spontaneous mutation in the genome because of selective pressures of the human immune surveillance system [Ramig, 1997], therefore, continuous monitoring of the prevalent rotavirus strains is important to identify new strains before they cause an epidemic [Ramachandran et al, 2000].…”
Section: Introductionmentioning
confidence: 99%